РЕФЛЕКСИИ НА ДУХОВНОТО КУЛТУРНО НАСЛЕДСТВО НА МАКЕДОНИЈА ВО НЕЈЗИНАТА ТОПОНИМИЈА (Filološke studije, 2019)
In this article we are analysing the toponymy as a part of the cultural heritage of the Republic of Macedonia. We have started from the assumption that the cultural heritage of a country consists of its language, religion, history and folklore. Consequently, first we were speaking about toponyms as linguistic signs in which very old lexemes and the earliest processes in the development of the language are reflected. After that we regarded the toponyms which reflect beliefs, customs and religion, and to that end we focused to the toponyms which reflect historic events. Accordingly, toponyms of the Republic of Macedonia justifiably were included in the Law on Protection of the Cultural Heritage of the Republic of Macedonia. The Krste Misirkov Institute for Macedonian Language, in Skopje was appointed as authorized body for protection of these toponyms by the Directorate for the Cultural Heritage of the Republic of Macedonia within the Ministry for Culture of the Republic of Macedonia. Unfortunately the toponyms in the Republic of Macedonia have not been included in the protection regime yet, since they are still in the process of valorisation.